The Impact of High-Intensity Interval Exercise Including Acceleration/Deceleration Patterns on Redox Status of Healthy Male Adults - Eleanna Chalari; Huw S. Jones; Marios Hadjicharalambous; Mark C. Fogarty (Applied Sciences, 2024)
High-intensity interval exercise (HIIE) is a type of structured physical training characterized by repeated bouts of high-intensity exercise interspersed with recovery periods. Although HIIE was found to improve physical performance in a relatively short period of time, there is emerging evidence suggesting that acute HIIE may induce oxidative stress. The purpose, therefore, of the present study was to examine the effect of intermittency and/or acceleration during HIIE on oxidative stress in male participants. Nine healthy males [(age: 21.0 ± 3.0 years; height: 180.0 ± 4.0 cm; body mass: 79.4 ± 7.9 kg; maximal oxygen uptake (<semantics><mover accent="true">V˙</mover></semantics>O2max) 52.0 ± 6.0 mL·kg−1·min−1)] were recruited to perform six distinct exercise protocols of various intermittency (high, medium, and low) and acceleration (high, medium, and low) while a control session was also included. Blood samples were obtained to determine oxidative stress indices (lipid hydroperoxides, superoxide dismutase, and total glutathione) at rest, 1 h, 2 h, and 24 h following exercise on a non-motorized treadmill. The intra-individual variability of participants was observed in lipid hydroperoxides at baseline, ranging from 1.80 to 20.69 μmol·L−1. No significant differences among the six different exercise protocols in any of the oxidative stress indices evaluated were observed (p > 0.05). These results suggest that the influence of various intermittency levels and acceleration patterns upon exercise-induced oxidative stress is negligible.